2014
DOI: 10.1111/josh.12217
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daily Physical Education on Physical Fitness and Weight Status in Middle School Adolescents

Abstract: Thirty minutes of daily PE can be considered a scientific approach to ameliorate health outcomes in at-risk middle school adolescents, particularly among females. Improvements on BMI percentile among at-risk youth are presaged by greater improvements in physical fitness. This investigation supports a school-based approach aimed to improve behavioral risk factors as a means to reduce childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 23 publications
3
41
1
2
Order By: Relevance
“…Although the present study had a cross-sectional design, the results found regarding participants who were not sports practitioners corroborate previous experimental studies that demonstrated increases in cardiorespiratory fitness [8][9][10] and muscle strength 8,9 after implementation of intervention programs within physical education classes. Likewise, they corroborate an observational study that was carried out on a representative sample in the American state of California.…”
Section: Discussionsupporting
confidence: 74%
“…Although the present study had a cross-sectional design, the results found regarding participants who were not sports practitioners corroborate previous experimental studies that demonstrated increases in cardiorespiratory fitness [8][9][10] and muscle strength 8,9 after implementation of intervention programs within physical education classes. Likewise, they corroborate an observational study that was carried out on a representative sample in the American state of California.…”
Section: Discussionsupporting
confidence: 74%
“…Andrew et al (2015) stated that physical education lessons should be conducted in middle schools for at least 225 minutes per week and that students should be physically active for a period of at least 50% of the physical education lessons. Erfle & Gamble (2015) concluded that a physical training programme implemented for 30 minutes per day for 1 academic year could be used as a means to increase regular physical activity and reduce obesity in childhood. Maria et al (2017) stressed that a well-structured physical education programme implemented and monitored by an expert physical training instructor would lead to improvement in children's motor skills and fitness levels.…”
Section: Discussionmentioning
confidence: 99%
“…In order to obtain these benefits (positive health effects) at least 60 minutes of regular physical activity are required per day (WHO, 2017). Regular physical activity in young people reduces the risk of childhood and adolescent obesity and decreases the risk of costly and fatal chronic diseases related to obesity (Erfle & Gamble, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis concluded that PE-based interventions result in children spending 10.4 % more lesson time in moderate-to-vigorous physical activity (MVPA) compared to regular PE lessons, which could have a significant contribution to total daily physical activity levels [18]. Moreover, there is evidence that PE interventions can positively impact on health-related fitness [19, 20] and motivational constructs, such as enjoyment [21]. In England, PE is a mandatory subject in schools through all years of compulsory schooling (ages 5 through 16 years).…”
Section: Introductionmentioning
confidence: 99%